Tuning the charge flow between Marcus regimes in an organic thin-film device - Atxabal, A. (Nat Commun, 2019)
Marcus’s theory of electron transfer, initially formulated six decades ago for redox reactions in solution, is now of great importance for very diverse scientific communities. The molecular scale tunability of electronic properties renders organic semiconductor materials in principle an ideal platform to test this theory. However, the demonstration of charge transfer in different Marcus regions requires a precise control over the driving force acting on the charge carriers. Here, we make use of a three-terminal hot-electron molecular transistor, which lets us access unconventional transport regimes. Thanks to the control of the injection energy of hot carriers in the molecular thin film we induce an effective negative differential resistance state that is a direct consequence of the Marcus Inverted Region.